New Views on the Misconstrued: Executioner Caspases and Their Diverse Non-apoptotic Roles - Unsain, Nicolas (2015)
Initially characterized for their roles in apoptosis, executioner caspases have emerged as important regulators of an array of cellular activities. This is especially true in the nervous system, where sublethal caspase activity has been implicated in axonal pathfinding and branching, axonal degeneration, dendrite pruning, regeneration, long-term depression, and metaplasticity. Here we examine the roles of sublethal executioner caspase activity in nervous system development and maintenance, consider the mechanisms that locally activate and restrain these potential killers, and discuss how their activity be subverted in neurodegenerative disease.